The design of a high speed topology for a QPSK demodulator with emphasis on the synchronization algorithms needed for demodulation - Booysen, Samuel (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.